Evaluating ballast water quality forcados terminal, Southern Delta, Nigeria - Umudi, Ese Queen; Umudi, Ogheneyoma Peter (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Forcados river terminal is deteriorated by anthropogenic and congenital exercises. The aim of this preliminary study is to assess ballast water through some pollution parameters as pH, electrical conductivity (EC), dissolved oxygen (DO), total alkalinity (TA), chlorine (Cl), nitrates (N), phosphate (P), turbidity (TB), lead (Pb), zinc (Zn), total dissolved solids (TDS), chromium (Cr), bacteria count (BC) and polynuclear aromatic hydrocarbons (PAHs). Maritime transport plays a major role due to its cost effectiveness and reliability. Ship-based marine pollution has a serious level for the environment, its biodiversity and economy. Results from the analysis showed that some parameters of ballast water from ships in Forcados (Chloride: 3.40-5.15 mg/l, phosphorus: 2.42-4.42 mg/l, turbidity: 18.70-23.51 mg/l, total dissolved solids: 270.31-341.21 mg/l) are not suitable for aquatic fauna. Hence, some special appraisal is needed. International Maritime Organization (IMO) regulations should be reviewed related to ballast water and local authorities should be educated on them before it is discharged into the river.